Association between immunization coverage and atopy in children with or without family history of atopic disease - Isabella Riandani; Budi Setiabudiawan; Cissy B. Kartasasmita (Indonesian Pediatric Society Publishing House, 2016)
Background Atopic diseases are determined by the interaction between genetic and environmental factors. The possible effects of immunization, as one of environmental factors, on atopy remain a matter of controversy. Objective We conducted an observational clinical epidemiology to find out the protective effect of high vaccination coverage to atopy in children. Methods During January through March 2006, 150 of749 children at Garuda, Padasuka, and Babakan Sari Primary Health Care in Bandung were randomized from group with and without family history of atopic disease. Atopy derived from skin prick test and total serum lgE was evaluated. Atopy was defined as a positive skin test to any of the eight allergens tested. The immunizations were recorded from Kartu Menuju Sehat (KMS). Statistical analyses included Chi square to compare prevalence, independent T-test and Mann-Whitney to compare mean. Results Atopy was found in 28.2% of284 subjects, of which 32.4% with and 23.9% without a family history of atopic disease. The median of total serum lgE level was higher in children with family history of atopic disease and in atopy children. Children were grouped according to total dose of basic immunizations (0-17 and 2: 18) based on Program Pengembangan Imunisasi (PPI). There was nonsignificant association between total doses of immunization and atopy. Even though no statistically significant, the cumulative immunization doses were inversely related to the median of total serum IgE level. Conclusions The immunization coverage has not decreased atopy risk.